POLYCLONAL ANTIBODY UTILIZATION FOR DETECTION OF JEMBRANA ANTIGEN AT BALI CATTLE IN WEST SUMATRA PROVINCE - Helmi Helmi; Endang Purwati; Ibnu Rahmadani; Didik Tulus Subekti (Jurnal Kedokteran Hewan, 2020)
The aims of this study were to detect Jembrana antigen with polyclonal antibody and to describe antigen distribution in the Bali cattle organ that positively infected with Jembrana disease. Spleens, lungs, and livers were harvested from 10 naturally infected Bali cattle whose infection was confirmed through positive Polymerase Chain Reaction (PCR) result for Jembrana virus. Immunohistochemistry test was performed using polyclonal antibodies produced in rabbits. The results showed that cells infected by Jembrana viruses displayed positive reaction with a reddish brown color. Immunohistochemistry methods using polyclonal antibodies can detect Jembrana antigens in the spleen, liver, and lung with the highest average detection score (P0.05) was found in spleen, followed by liver and lungs. There was significant difference in the distribution of Jembrana antigens between the spleen, liver, and lungs with spleen having the highest antigen density.